Effect of microbial inoculants with low dose of inorganic fertilizers on microbial growth, soil enzymes, plant growth and yield of rice - Jeya Bharathi, M; Rajappan, K (ORYZA-An International Journal of Rice, 2019)
Continuous application of chemical fertilizers alters the soil biological properties and in situ causes residual effect on the crop plants. Field experiments were conducted with microbial inoculants and reduced inorganic fertilizers. The results of the experiments showed that application of 50 % recommended dose of nitrogen (N), phosphorous (P) and potassium (K) + azolla+ azophos + K releasing bacteria (KRB) + zinc solubilizing bacteria (ZSB) was found to have maximum soil microbial population viz., azospirillum (5.4 MPN/g), phosphobacteria (54 x 104 cfu/g) and diazotrophs (56 x104 cfu/g) under system of rice intensification (SRI) ecosystem, while 25 % recommended dose of NPK + azolla + azophos + KRB + ZSB was found to have maximum soil alkaline phosphatase (538 μg of P nitrophenol/g/h), acid phosphatase (248 μg of P nitrophenol/g/h), urease (79 μg of NH4/g/24 hrs) and dehydrogenase (110 μg of TPF/g/24 h) enzyme activity under SRI ecosystem. Among the treatments, maximum N (357 kg/ha), P (93 kg/ha), K (315 kg/ha) and yield (6800 kg/ha) was found in the treatment 100% recommended dose of NPK which was found to be on par with the yield (6850 kg/ha) under 50% recommended dose of NPK + azolla+ azophos + KRB + ZSB under SRI ecosystem.